Simulation Environment for Analysis and Controller Design of Diesel Engines. Issue 2 (2020) - Nguyen, Hoang Khac; Modabberian, Amin; Zenger, Kai; Storm, Xiaoguo; Hyvönen, Jari
Abstract: Novel combustion concepts and multi-injection cylinder-wise control methods are needed in large marine diesel engines for increased performance and to reduce the green house gas emissions. Even though diesel technology in cars might be reducing there is no replacement of dual fuel diesel technology in large marine engines to be seen in the near future. The paper discusses a rapid grey-box modeling technique, which can be used to predict cylinder pressure and heat release in engine cylinders. The model can be used to design effective cylinder-wise control algorithms which increase the engine performance and save fuel under constraint of emissions.